'It's on your conscience all the time': a systematic review of qualitative studies examining views on obesity among young people aged 12–18 years in the UK. Issue 4 (30th April 2014) - Rees, Rebecca W; Caird, Jenny; Dickson, Kelly; Vigurs, Carol; Thomas, James
Abstract : Objective: To explore the perspectives of young people in the UK on obesity, body size, shape and weight. Design: Systematic review of qualitative studies using thematic synthesis. Data sources: Sensitive searches of 18 electronic databases from 1997 to February 2010 supplemented by grey literature searches. Study selection: Studies produced since 1997 using qualitative methods to collect perspectives of people aged 12–18 years in the UK, reporting methods for data collection or analysis. Studies of people with eating disorders and those rated low in reliability and usefulness were excluded. Results: Searches identified 30 studies involving over 1400 young people from a range of contexts. Young people of all sizes placed considerable emphasis on personal responsibility, and on the social, rather than health implications of being overweight. Young people with experience of obesity described severe, unrelenting, size-related abuse and isolation. Regardless of their own size, young people were judgemental of individuals who were overweight, but those with experience of obesity described an environment that contained multiple barriers to weight loss. Only one study asked young people directly what might support them to have a healthy body size. Study findings were configured under three main themes, labelled with quotes from included studies: general perceptions of size and society's responses ('It's on your conscience all the time'); the experiences of young people who were overweight ('If I had the choice I wouldn't be this size') and these larger young people's experiences of trying to loose weight and suggestions for action ('Make sure, even when it's hard, you've got people there'). Conclusions: The perspectives of young people in the UK, when synthesised across the spectrum of body sizes, paint a picture of a stigmatising and abusive social world. Research and policy need to engage young people actively so as to address the social implications of obesity.